A novel method for superimposition and measurements on maxillary digital 3D models—studies on validity and reliability. (22nd April 2017) - Ganzer, Niels; Feldmann, Ingalill; Liv, Per; Bondemark, Lars
Summary: Background: Serial 3D models can be used to analyze changes, but correct superimposition is crucial before measurements can be assessed. Earlier studies show that every palatal structure changes due to growth or treatment. Here, we describe a new method that uses an algorithm-based analysis to perform superimpositions and measurements in maxillary 3D models. This method can be used to identify deformations. In a second step, only unchanged areas are used for superimposition. Objectives: This study investigates the validity and reliability of this novel method. Methods: Digital 3D models from 16 cases were modified by an independent 3D engineer to simulate space closure and growth. True values for tooth movements were available as reference. Measurements and repeated measurements were performed by four observers. Results: The total tooth movement had an absolute mean error of 0.0225 mm (SD 0.03). The intraclass correlation coefficient (ICC) was 0.9996. Rotational measurements had an absolute mean error of 0.0291 degrees (SD 0.04 degrees) and an ICC of 0.9999. Limitations: Serial models need to be taken with a moderate interval (1 to 2 years). Obvious changed areas in the palate need to be cropped before processing the models. Conclusion: The tested method is valid and reliable with excellent accuracy and precision even when changes through growth or orthodontic treatment occur.